2021
DOI: 10.1101/2021.06.29.450322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The endoplasmic reticulum-resident protein TMEM-120/TMEM120A promotes fat storage in C. elegans and mammalian cells

Abstract: The synthesis of triacylglycerol (TAG) is essential for the storage of excess fatty acids, which can subsequently be used for energy or cell growth. A series of enzymes act in the endoplasmic reticulum (ER) to synthesize TAG, prior to its transfer to lipid droplets (LDs), which are conserved organelles for fat storage. Here, we report that the deficiency of TMEM-120/TMEM120A, a protein with 6-transmembrane helices, retards TAG synthesis and LD expansion in C. elegans. GFP fusion proteins of TMEM-120, expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…TMEM120A was shown earlier to be present in the plasma membrane using cell-surface biotinylation ( Beaulieu-Laroche et al, 2020 ; Chen et al, 2022 ), but it was also shown to be localized to the endoplasmic reticulum ( Li et al, 2021 Preprint ) and the nuclear envelope ( Batrakou et al, 2015 ). Consistent with these earlier data, TMEM120A-tdTomato showed not only plasma membrane, but also substantial intracellular localization in confocal microscopy experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TMEM120A was shown earlier to be present in the plasma membrane using cell-surface biotinylation ( Beaulieu-Laroche et al, 2020 ; Chen et al, 2022 ), but it was also shown to be localized to the endoplasmic reticulum ( Li et al, 2021 Preprint ) and the nuclear envelope ( Batrakou et al, 2015 ). Consistent with these earlier data, TMEM120A-tdTomato showed not only plasma membrane, but also substantial intracellular localization in confocal microscopy experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TMEM120A and TMEM120B (a closely related homolog) are both highly expressed in white and brown adipose tissue [ 19 ]. A knockdown of Tmem120A , Tmem120B , or both in premature adipocytes (3T3-L1 and OP9 cells) prevents triglyceride accumulation and gene expression indicative of maturation [ 19 , 21 ]. Reintroducing TMEM120A to knockdown cells fully rescues the phenotype, while TMEM120B has only a partial effect [ 19 ].…”
Section: Tmem120a Regulates Lipid Metabolismmentioning
confidence: 99%
“…How TMEM120A mechanistically affects lipids may depend on its debated sub-cellular localization. One group identified TMEM120A in the nuclear envelope and the endoplasmic reticulum (ER) [ 51 ], two found it in the ER [ 21 , 22 ], and three more claimed it was localized in the plasma membrane [ 9 , 17 , 24 ]. Those finding TMEM120A in the nuclear envelope identified altered gene expression of key regulators for adipocyte maturation [ 19 ] and metabolism [ 20 ] when it was knocked down or out, respectively.…”
Section: Tmem120a Regulates Lipid Metabolismmentioning
confidence: 99%
“…[37] A recent paper also showed that TMEM120A can promote TAG (Tria- cylglycerol) synthesis which is essential for the storage of excess fatty acids in C. elegans. [38] Both the structural and physiological studies suggest that TMEM120A has a crucial role in fatty acid metabolism. Regarding its molecular mechanism, TMEM120A has been reported to function in the expression regulation of adipogenic genes, [38][39][40] but it is still unclear how the protein selectively regulates the genome loci supporting adipogenesis.…”
Section: Tmem120a: a Fatty Acid Elongase?mentioning
confidence: 99%
“…[38] Both the structural and physiological studies suggest that TMEM120A has a crucial role in fatty acid metabolism. Regarding its molecular mechanism, TMEM120A has been reported to function in the expression regulation of adipogenic genes, [38][39][40] but it is still unclear how the protein selectively regulates the genome loci supporting adipogenesis. Further investigation is needed to provide the mechanism underlying the potential connections between TMEM120A and fatty acid metabolism.…”
Section: Tmem120a: a Fatty Acid Elongase?mentioning
confidence: 99%